2017
DOI: 10.1038/s41598-017-07809-1
|View full text |Cite
|
Sign up to set email alerts
|

A metastable phase of shocked bulk single crystal copper: an atomistic simulation study

Abstract: Structural phase transformation in bulk single crystal Cu in different orientation under shock loading of different intensities has been investigated in this article. Atomistic simulations, such as, classical molecular dynamics using embedded atom method (EAM) interatomic potential and ab-initio based molecular dynamics simulations, have been carried out to demonstrate FCC-to-BCT phase transformation under shock loading of 〈100〉 oriented bulk single crystal copper. Simulated x-ray diffraction patterns have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…These observations suggest that during stretching deformation along [110] and [111] direction the phase transformations are not thorough and complete. This result is fully consistent with Neogi's simulation investigation on shock-induced phase transformations of single crystal copper [28,29].…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 1 more Smart Citation
“…These observations suggest that during stretching deformation along [110] and [111] direction the phase transformations are not thorough and complete. This result is fully consistent with Neogi's simulation investigation on shock-induced phase transformations of single crystal copper [28,29].…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…Mitra [28,29] discovered the phase transformation behavior induced by shock compression of single crystal Cu via classical MD simulations as well as ab−initio MD simulations. They found that during shock wave propagation along [100] and…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Despite these great progresses, the pursuit of non‐FCC Cu has been unexpectedly sluggish . Till now, the only viable method is to deposit a metastable ultrathin Cu film on another metal substrate (such as W{001}) under ultrahigh vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these great progresses, the pursuit of non‐FCC Cu has been unexpectedly sluggish . Till now, the only viable method is to deposit a metastable ultrathin Cu film on another metal substrate (such as W{001}) under ultrahigh vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24] Despite these great progresses,the pursuit of non-FCC Cu has been unexpectedly sluggish. [25][26][27] 12 Cl featuring aC u 13 icosahedron core was first reported in 2015. [28] AC u 13 cuboctahedron and Cu 20 NCs were also captured very recently.…”
Section: Introductionmentioning
confidence: 99%